Is Low-free Triiodothyronine (fT3) Associated with Increased Morbidity in Patients Admitted to Coronary Care Units? - Akkuş, Oğuz; Şen, Fatih; Yasdıbaş, Ramazan; Ötegen, Alper Tunga; Hüzmeli, İrem and Akkuş, Gamze (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundThe effects of thyroid hormone on patients hospitalized in coronary intensive care units are still controversial.ObjectiveWe retrospectively examined thyroid hormone levels and their impact on cardiovascular morbidity in patients admitted to coronary intensive care units.MethodsA total of 208 (Female/Male; 46.6%/53.4%) patients without any history of thyroid disease were enrolled and screened. Patients with specific heart disease and existing thyroid hormone parameters were included in the study. Low triiodothyronine syndrome is characterized by reduced serum total or free T3 (fT3) concentrations in normal free T4 (fT4) and TSH levels.ResultsThe common diagnosis of the patients in the coronary care unit is acute coronary syndrome (n = 59, 28.2%) and heart failure (n = 46, 23.3%). Patients were divided into two groups according to left ventricular ejection fraction percentages (LVEF ≤39% vs LVEF ≥40%). Plasma fT3 levels were significantly correlated with low LVEF (≤39%) (p =0.002). fT3 (r = -0.183, p =0.013) and hospitalization etiology (r = -0.161, p =0.023) were also the most critical parameters affecting the length of hospitalization.ConclusionLow fT3 was associated with reduced ejection fraction and prolonged hospitalization, which may lead to potential morbidities in HF patients and may be useful in risk stratification and treatment strategies.
Keywords: patients